Technological entry in new niches: Diversity, crowding and generalism. (August 2022) - Candiani, Juan Antonio; Gilsing, Victor; Mastrogiorgio, Mariano
Abstract: Entry in new technological domains is essential for the long-term performance of firms. Therefore, it is important to understand the conditions that increase the likelihood that firms enter, and further explore, new technological domains. Some recent studies have started to unpack these issues by looking at the environmental conditions in a new technological domain that pull firms into it. In this paper, we complement these studies by looking at the environmental conditions in the firm's current technological domain that push firms into new domains. We do it from the perspective of technological ecology, by looking at how technological diversity and crowding in the firm's current technological niche, as well as firm's knowledge generalism, affect the likelihood that the firm enters, and further explores, new technological niches. To test our hypotheses, we rely on an empirical setting based on U.S. patents by 340 firms in the pharmaceutical industry. We propose a novel and advanced approach that, by leveraging a vast set of technological classifications, extracts technological niches from the patent system as they evolve over time. Highlights: The paper examines the conditions increasing the likelihood of a firm's entry and exploration of new technological niches. The paper examines the push conditions in the current niche of the firm: technological diversity, crowding, and generalism. To measure technological niches, we leverage on a vast set of technological classifications in the US patent system.